A companion to epistemology - Dancy, Jonathan; Sosa, Ernest (Blackwell companions to philosophy., 1993)
Epistemology - the theory of knowledge and of justified belief - has always been of central importance in philosophy. Progress in other areas of philosophical research has often depended crucially on epistemological presuppositions. This Companion, with well over 250 articles ranging from summary discussions to major essays on topics of current controversy, is the first complete reference work devoted to the subject. All the main theoretical positions in epistemology are discussed and analysed, tougher with the different categories of knowledge itself - scientific, historical, mathematical, a priori, moral and so on - and the special problems associated with these. There are also many entries covering individual concepts, arguments and problems, short definitions of technical terms, and biographical articles.With its unrivalled coverage of the field, supported by a comprehensive index and an extensive cross-referencing, the Companion is likely to remain the standard reference work in epistemology from undergraduate level upward for the foreseeable future.